Management of gynaecologic plasmacytoma: A review article. (2nd January 2017) - Feldman, Aharon M; Zhang, Ziying; Buekers, Thomas; Elshaikh, Mohamed A
Abstract: In contrast to multiple myeloma (MM) which exhibits diffuse bone marrow and other organ involvement, solitary plasmacytomas carry a favourable prognosis. Extramedullary plasmacytomas (EMP) are a unique form of plasma cell neoplasms. These tumours are rare in the female reproductive tract. Only 24 cases of gynaecologic plasmacytomas were reported to date (7 cases were solitary plasmacytomas and 17 cases were either part of disseminated MM with involvement of a gynaecologic organ or were lacking complete work-up to rule out MM). The standard care of gynaecologic solitary EMP is surgical resection alone when feasible. Adjuvant radiation therapy may be considered for adverse prognostic factors such as positive resection margins. MM with gynaecologic organ involvement should be managed with systemic therapy and defer local therapies to symptomatic progression.